Effect of Eco Enzymes Concentration on Growth and Production of Kembang Telang Plant(Clitoria ternatea L.) as Animal Feed - Sembiring, S. D. B. J.; Ginting, N.; Umar, S.; Ginting, S. (Talenta Publisher, 2021)
KembangTelang plant is a legume that contains high protein for animal feed.This research aim to investigate the effect of giving Eco Enzymes (EE) at different concentration on the growth and production of KembangTelang plant (Clitoria ternatea L.) and it was conducted at the Compost Center, Faculty of Agriculture, University of North Sumatra from October to December 2020. Research design was used a completely randomized design with two factors, namely Eco Enzymes concentration and watering application using plant infusion which was regulated by dropping rate. There were 3 treatments and 3 replications. The first factor were the concentration of Eco Enzymes, i. e K1=1% , K2=0,5%, K3=0,33%. The second factor were watering with a plant infusion system or a regulated dropping rate, T1= slow drop, T2= medium drop, and T3= quick drop. The parameters observed were plant height, number of leaves, number of branches, stem diameter, leaf width, production of fresh matter and production of dry matter.The results showed that the concentration of Eco EnzymesK1 1% gives a very real effect (P< 0.01) on the parameters of plant height, number of leaves, number of branches, and production of fresh matter, while on the parameters of stem diameter gives a real influence (P<0.05), and gives an unreal influence (P>0.05) on the parameters of leaf width, dry matter production and the use of plant infusion. The best response of Eco Enzymes administration was of 1% concentration.